Aktivitas Kombinasi Ekstrak Daun Sirsak (Annona muricata Linn) dan Kulit Buah Naga (Hylocereus polyrhizus) pada Staphylococcus aureus dan Escherichia coli - Suprianto; Sri Zuwinda Zusya Pane; Sumardi (Yayasan Penelitian dan Inovasi Sumatera, 2026)
Background: Bacterial infections caused by Staphylococcus aureus and Escherichia coli remain clinically relevant due to their ability to cause skin and gastrointestinal infections. The growing concern over antimicrobial resistance has increased interest in plant-derived antibacterial agents. Soursop leaves (Annona muricata L.) and red dragon fruit peel (Hylocereus polyrhizus) contain secondary metabolites that may contribute to bacterial growth inhibition. Objective: This study aimed to evaluate the antibacterial activity of combined ethanolic extracts of A. muricata leaves and H. polyrhizus peel against S. aureus and E. coli, and to determine the most effective extract ratio based on inhibition zone diameter. Methods: This laboratory experimental study used the disc diffusion method on Nutrient Agar medium. The plant materials were extracted by maceration using 70% ethanol. Five extract ratios were tested, namely 0.05:2.95, 0.10:2.90, 0.15:2.85, 0.20:2.80, and 0.25:2.75. Amoxicillin was used as the positive control, while distilled water served as the negative control. Inhibition zones were measured after 24 hours of incubation at 37°C. Results: The extract combinations showed weak antibacterial activity against S. aureus, with mean inhibition zones ranging from 1.08 to 3.18 mm. Against E. coli, four ratios showed weak activity, while the 0.25:2.75 ratio produced moderate inhibition with the highest mean zone of 5.18 mm. The positive control produced a strong inhibition zone of 13.13 mm, whereas the negative control showed no inhibition. Conclusion: The combination of A. muricata leaf and H. polyrhizus peel extracts demonstrated limited antibacterial activity and did not indicate a strong synergistic effect. The 0.25:2.75 ratio showed the best activity against E. coli and may be considered for further optimization using higher concentrations and more specific antibacterial assays.